2017
DOI: 10.1017/s0025100317000275
|View full text |Cite
|
Sign up to set email alerts
|

Argentine Spanish

Abstract: Although Spanish is a relatively unified language, in the sense that people from very distant locations manage to understand each other well, there are several phonetic phenomena that distinguish geographically separated varieties. The total number of native speakers of Spanish is above 400 million, and roughly 10% of them live in Argentina (Instituto Cervantes 2014). The accent described below corresponds to formal Spanish spoken in Buenos Aires, and the main allophones are indicated by parentheses in the Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The only clue comes from Zabala et al (2016:160), who state that the noise frequency of palato-alveolar /ʃ/ can change depending on the formants of the neighbouring vowels, referring to García Jurado (2005), according to whom /ʧi/ has an initial transition frequency of 2.146 Hz, while that of /ʧo/ is 1.735 Hz. Apart from this documentation of an expected coarticulation process, there are no indications in the phonetic descriptions of Argentine Spanish that coarticulatory labialization should be a prominent or inherent feature of /ʧ/ (or other fricatives) (Lipski 1994:168-172, Harris & Kaisse 1999, Baker & Wiltshire 2003, Hualde 2005, Chang 2008, Kochetov & Colantoni 2011, Colomá 2018). Further research is required to establish whether this is because /ʧ/ is not generally labialized, or whether labialization before rounded vowels is considered a natural process of coarticulation and therefore does not attract attention.…”
Section: Eldoradomentioning
confidence: 91%
“…The only clue comes from Zabala et al (2016:160), who state that the noise frequency of palato-alveolar /ʃ/ can change depending on the formants of the neighbouring vowels, referring to García Jurado (2005), according to whom /ʧi/ has an initial transition frequency of 2.146 Hz, while that of /ʧo/ is 1.735 Hz. Apart from this documentation of an expected coarticulation process, there are no indications in the phonetic descriptions of Argentine Spanish that coarticulatory labialization should be a prominent or inherent feature of /ʧ/ (or other fricatives) (Lipski 1994:168-172, Harris & Kaisse 1999, Baker & Wiltshire 2003, Hualde 2005, Chang 2008, Kochetov & Colantoni 2011, Colomá 2018). Further research is required to establish whether this is because /ʧ/ is not generally labialized, or whether labialization before rounded vowels is considered a natural process of coarticulation and therefore does not attract attention.…”
Section: Eldoradomentioning
confidence: 91%
“… See IPA (1912),IPA (1949) andIPA (1999), or the many "Illustrations of the IPA" published in the Journal of the International Phonetic Association since 1990. 2 Other (slightly different) versions appear in Avelino (2017) and inColoma (2017). 3 See, for example,Bowern, McDonough & Kelliher (2012).…”
mentioning
confidence: 99%
“…The consonant phoneme inventory of the variety of Argentine Spanish is described in Table 3 below (Coloma, 2018) Previous research on lenition of stop consonants in Argentine Spanish has found lenition of voiced stops in this dialect. For example, Colantoni & Marinescu (2010) found that target voiced stops were consistently realized as approximants and some of the voiced tokens were deleted, and there were fewer signs of weakening in the voiceless stops.…”
Section: Argentine Spanishmentioning
confidence: 99%